NM23HI as marker of metastasis in invasive ductal breast cancer - Rustamadji, Primariadewi (Acta medica Indonesiana, 2012)
to examine the presence of metastasis marker in various histological malignancies of ductal breast carcinoma using NM23HI protein. paraffin blocks were obtained from 97 patients with invasive breast ductal cancer with 1, 2, 3 grade of malignancy from 2000 to early 2006 in several hospitals in Jakarta and Bandung. Examination began with histophatologic examination of eosin hematoxylin slides to diagnose the case of invasive ductal cancer and to get the data on the degree of histologic malignancy, metastasis or non-metastasis cases. It then continued to immunohistochemistry examination of NM23HI, and cytokeratin. subjects were 29-75 years old with the mean of 48.19 years; most subjects were 40-45 years old with malignancy grade 1 numbering 18.56%; grade 2, 45.36%; and grade 3, 36.1%. Ninety seven paraffin blocks were examined from 2000 to 2006. There was a significant relationship between NM23HI expression in primary tumor with the possibility of inhibition of invasion and metastasis 11 times of those of negative expression of NM23HI. The ROC curve showed that NM23HI expression was strongly correlated (r=0.816) sensitive and specific as metastasis marker. NM23HI expression did not show significant relationship with histologic degree of invasive ductal carcinoma. NM23HI expressions can be used as invasion and metastasis markers, but cannot be used as markers for the degree of histologic malignancy of invasive ductal cancer.